NAfMA as a value creation tool: Malaysian scenario / Suzana Sulaiman, Normah Omar and Ibrahim Kamal Abdul Rahman - Sulaiman, Suzana; Omar, Normah; Abdul Rahman, Ibrahim Kamal (Accounting Research Institute (ARI) & Faculty of Accountancy, 2005)
The National Award for the Management Accounting (NAfMA) Best Practice 2004 is the first of its kind in the Asian region. For a start, NAfMA 2004 is open to Malaysian Multi-national and Public-Listed Companies (PLC). As Malaysia strives to become fully industrialized, it is believed that embracing best practices in management accounting will ensure that businesses are using the appropriate tools and techniques to achieve optimum business performance, resulting in value creation. Through the spirit of sharing best practices and benchmarking amongst with other organisations it will also enable companies in Malaysia to move towards world-class recognition. The NAfMA Best Practice is assessed on the basis of the management accounting best practice conceptual framework proposed by the International Federation of Accountants (IFAC). The participating companies were assessed on criteria, which include management accounting information, leadership, resource management, customer/market focus, partnership management, value creating, business results/performance measurement and corporate social responsibility. These criteria were finalized after numerous discussions between several parties involved. An independent panel of assessors made a second site visit to those short-listed companies. Recommendations resulting from a team of independent assessors were then put to the panel of judges before the recipients were decided.